Modifying the rheological properties, in vitro digestion, and structure of rice starch by extrusion assisted addition with bamboo shoot dietary fiber. (1st May 2022) - Wang, Nan; Wu, Liangru; Zhang, Fusheng; Kan, Jianquan; Zheng, Jiong
Graphical abstract: Highlights: Bamboo shoot dietary fiber (BSDF) increased viscoelasticity and thixotropy of extruded starch. The content of rapid digestion starch decreased after extrusion-assisted BSDF addition. The surface of starch granules gradually became loose and rough with increasing content of BSDF. The relative crystallinity and branching degree of extruded starch increased with BSDF addition. Abstract: This paper investigated the effect of extrusion treatment on the rheological properties, in vitro digestibility, and multi-structure of starch with or without bamboo shoot dietary fiber (BSDF). The viscoelasticity and thixotropy decreased after extrusion treatment, however, they increased after BSDF addition, and decreased with increasing BSDF content. The starch granules became smooth and formed big lumps after extrusion treatment. The dense lumps became loose after the addition of BSDF. Extrusion treatment changed the movement and arrangement of starch chains and thus the relative crystallinity and branching degree decreased by 92.6% and 40.9%, respectively. The disruption of starch further increased rapid digestion starch (RDS) content by 10%. The decreased disruption of starch granules and increased entanglement between BSDF and starch decreased the RDS content. The addition of BSDF is a novelty method to enhance the nutritional properties and control the physicochemical properties of extruded starchy foods.